The Influence of Leverage, Firm Size, Liquidity, and Profitability on Earnings Quality in Industrial Sector Companies Listed on the Indonesia Stock Exchange - Rini Nur Rachmawati; Sunarto Sunarto (Journal of Social Research, 2025)
This research examines corporate earnings quality. Earnings quality is measured using net profit before tax and operating cash flow. The primary objective of this research is to examine how leverage, company size, liquidity, and profitability influence earnings quality in the industrial sector listed on the Indonesia Stock Exchange (IDX). Sampling was conducted using purposive sampling, focusing on the research period between 2022 and 2024. Data were taken from publicly traded manufacturing companies with positive operating cash flow and profits. Initially, 311 samples were generated, but after a normality test, the sample size was reduced to 234. The correlation and/or relationship between variables was explained using the t-test method. The findings of this study indicate that leverage followed by profitability significantly affects earnings quality. Because higher leverage and profitability result in lower errors, the lower the error, the higher the earnings quality. Meanwhile, company size followed by liquidity is not significant on earnings quality. Because lower size and liquidity result in higher errors, the higher the error, the lower the earnings quality.